GENETICS FOR DIAGNOSTICS IN PREVENTIVE MEDICINE - I. V. Sidonets; A. N. Meshkov (Кардиоваскулярная терапия и профилактика, 2014)
The sequencing of first human genome followed by rapid development of technologies, that led to significant lowering of costs for genetic analyze and its fast performing, made possible a broad invention of genetic diagnostics methods into clinical practice. Contemporary methods of molecular genetics make possible to research on inherited factors on chromosome level with molecular cytogenetics methods, and on the level of local mutations with the use or polymeraze chain reaction, microchips and sequencing. Temps of the next generation sequencing methods provide the opportunity to predict soon inclusion in practice of the personalized medical analysis of large genetic data massive, that can be used for the disease outcome prediction, estimation of its course, and for the prescription and correction of pharmacotherapy. In this review, different (including novel) approaches to genetic diagnostics are explored for the rare as common diseases, their benefits and restrictions.